LNA oligonucleotide mediates an anti-inflammatory effect in autoimmune myocarditis via targeting lactate dehydrogenase B - Bockstahler, Mariella; Salbach, Christian; Müller, Anna-Maria; Kübler, Andrea; Müller, Oliver J.; Katus, Hugo; Frey, Norbert; Kaya, Ziya (Immunology, 2022)
Treatment of myocarditis is often limited to symptomatic treatment due to unknown pathomechanisms. In order to identify new therapeutic approaches, the contribution of locked nucleic acid antisense oligonucleotides (LNA ASOs) in autoimmune myocarditis was investigated. Hence, A/J mice were immunized with cardiac troponin I (TnI) to induce experimental autoimmune myocarditis (EAM) and treated with LNA ASOs. The results showed an unexpected anti-inflammatory effect for one administered LNA ASO MB_1114 by reducing cardiac inflammation and fibrosis. The target sequence of MB_1114 was identified as lactate dehydrogenase B (mLDHB). For further analysis, mice received mLdhb-specific GapmeR during induction of EAM. Here, mice receiving the mLdhb-specific GapmeR showed increased protein levels of cardiac mLDHB and a reduced cardiac inflammation and fibrosis. The effect of increased cardiac mLDHB protein level was associated with a downregulation of genes of reactive oxygen species (ROS)-associated proteins, indicating a reduction in ROS. Here, the suppression of murine pro-apoptotic Bcl-2-associated X protein (mBax) was also observed. In our study, an unexpected anti-inflammatory effect of LNA ASO MB_1114 and mLdhb-specific GapmeR during induction of EAM could be demonstrated in vivo. This effect was associated with increased protein levels of cardiac mLDHB, mBax suppression and reduced ROS activation. Thus, LDHB and LNA ASOs may be considered as a promising target for directed therapy of myocarditis. Nevertheless, further investigations are necessary to clarify the mechanism of action of anti-inflammatory LDHB-triggered effects.